2014
DOI: 10.1364/oe.22.016099
|View full text |Cite
|
Sign up to set email alerts
|

Coherent optical non-reciprocity in axisymmetric resonators

Abstract: We describe an approach to optical non-reciprocity that exploits the local helicity of evanescent electric fields in axisymmetric resonators. By interfacing an optical cavity to helicity-sensitive transitions, such as Zeeman levels in a quantum dot, light transmission through a waveguide becomes direction-dependent when the state degeneracy is lifted. Using a linearized quantum master equation, we analyze the configurations that exhibit non-reciprocity, and we show that reasonable parameters from existing cavi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 43 publications
(74 reference statements)
0
27
0
Order By: Relevance
“…In conventional nonreciprocal optical devices, this is induced by a magnetic field in conjunction with magneto-optical materials, the time modulation of the optical properties of the system, or an optical nonlinearity. Non-reciprocity that relies on chiral coupling to break Lorentz reciprocity, however, can be based solely on the atomic spin, which is in general associated with a polarization-dependent coupling strength to realize optical isolators and circulators [49,50]. Optical isolators and circulators utilizing chiral coupling to achieve non-reciprocal absorption or phase shifts have been demonstrated with either a small ensemble of atoms coupled to an optical nanofiber, cf.…”
Section: Elementary Devices Based On Chiral-light Matter Interactionmentioning
confidence: 99%
“…In conventional nonreciprocal optical devices, this is induced by a magnetic field in conjunction with magneto-optical materials, the time modulation of the optical properties of the system, or an optical nonlinearity. Non-reciprocity that relies on chiral coupling to break Lorentz reciprocity, however, can be based solely on the atomic spin, which is in general associated with a polarization-dependent coupling strength to realize optical isolators and circulators [49,50]. Optical isolators and circulators utilizing chiral coupling to achieve non-reciprocal absorption or phase shifts have been demonstrated with either a small ensemble of atoms coupled to an optical nanofiber, cf.…”
Section: Elementary Devices Based On Chiral-light Matter Interactionmentioning
confidence: 99%
“…More recently, polarization selectivity has brought a new dimension to cavity QED. For example, accessing specific sublevels using polarized light can merge time-reversal symmetry breaking into chiral photonics [12][13][14]. Although individual atoms allow strong coupling in circularly-polarized cavity QED [15], the degenerate valley-specific excitons of transition metal dichalcogenides (TMDs) are a model material system for achieving polarization selectivity with bosonic excitonpolaritons ( Fig.…”
mentioning
confidence: 99%
“…It has already been shown that the breaking of Lorentz reciprocity is pivotal for isolators [20]. One class of nonreciprocal systems which can be used for isolators and circulators is based on the breaking of the time-reversal symmetry.In general, the breaking of time-reversal symmetry in optical systems can be generated by two different ways: (i) using magneto-optical effects (e.g., Faraday rotation) [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and (ii) non-magnetic strategies (e.g., employing optical nonlinearity [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], dynamical modulation [51-75], etc). Especially, as a non-magnetic strategy, optical nonreciprocity in the coupled cavity modes with relative phase has drawn more and more attentions in recent years, and many differ- * Electronic address: davidxu0816@163.com…”
mentioning
confidence: 99%